A monoclonal antibody against antigen-specific helper factor augments T-cell help. - James, R; Kontiainen, S; Maudsley, D; Culbert, E; Feldmann, M (1983)
Antigen-specific molecules, commonly termed 'factors', have been shown to be released from helper and suppressor T cells. These factors mimic the activity of the cells that secrete them and there is much speculation about the relationship of antigen-specific factors to T-cell receptors for antigen. We have raised a variety of antisera in rabbits which were shown to react against conserved 'constant' determinants on either helper or suppressor factors independently of antigenic specificity or mouse strain of origin of the factor. In contrast, syngeneic mouse antisera were found to react with 'variable' factor determinants in an antigen-specific and mouse strain-dependent manner. These antisera thus define two regions on factor molecules, one 'variable' (related to antigen specificity) and the other 'constant' (related to function). However, potential contaminants in these antisera have limited their usefulness. Thus, we are now generating monoclonal antibodies against T-cell factors and report here the properties of a monoclonal antibody (AF3.44.4) which reacts with antigen-specific helper factors. This antibody also binds to helper T cells and, in the presence of antigen, augments helper cell induction in vitro, which, in turn, leads to enhanced antibody production in vitro. These characteristics suggest that AF3.44.4 recognizes a determinant shared by helper factor and the antigen receptor on helper T cells.